Optical tomography of the aurora and EISCAT - H. U. Frey; S. Frey; B. S. Lanchester; M. Kosch (Annales Geophysicae, 1998)
Tomographic reconstruction of the three-dimensional auroral arc emission is used to obtain vertical and horizontal distributions of the optical auroral emission. Under the given experimental conditions with a very limited angular range and a small number of observers, algebraic reconstruction methods generally yield better results than transform techniques. Different algebraic reconstruction methods are tested with an auroral arc model and the best results are obtained with an iterative least-square method adapted from emission-computed tomography. The observation geometry used during a campaign in Norway in 1995 is tested with the arc model and root-mean-square errors, to be expected under the given geometrical conditions, are calculated. Although optimum geometry was not used, root-mean-square errors of less than 2% for the images and of the order of 30% for the distribution could be obtained. The method is applied to images from real observations. The correspondence of original pictures and projections of the reconstructed volume is discussed, and emission profiles along magnetic field lines through the three-dimensionally reconstructed arc are calibrated into electron density profiles with additional EISCAT measurements. Including a background profile and the temporal changes of the electron density due to recombination, good agreement can be obtained between measured profiles and the time-sequence of calculated profiles. These profiles are used to estimate the conductivity distribution in the vicinity of the EISCAT site. While the radar can only probe the ionosphere along the radar beam, the three-dimensional tomography enables conductivity estimates in a large area around the radar site. Key words. Tomography · Aurora · EISCAT · Ionosphere · Conductivity